Determination of 55-155-155-1in second order QCD from hadronic Z decays - Abreu, P; Adam, W; Adami, F; Adye, T; Akesson, T; Alekseev, G; Allen, P; Almehed, S; Alvsvaag, S; Amaldi, U; Anassontzis, E; Antilogus, P; et al. (1992)
Distributions of event shape variables obtained from 120600 hadronic Z decays measured with the DELPHI detector are compared to the predictions of QCD based event generators. Values of the strong coupling constant αs are derived as a function of the renormalization scale from a quantitative analysis of eight hadronic distributions. The final result, αs(MZ), is based on second order perturbation theory and uses two hadronization corrections, one computed with a parton shower model and the other with a QCD matrix element model. © 1992 Springer-Verlag.